GROWTH EFFECTS OF INFORMATION AND COMMUNICATION TECHNOLOGIES: EMPIRICAL EVIDENCE FROM THE ENLARGED EU - Karagiannis, Stelios; Feridun, Mete (Vilnius Univ, 2009)
The present article explores the impact of Information and Communication Technologies (ICT) on the output growth of the EU industries in lite enlarged European Union (EU-25). Emphasis is given on the effects arising from the older member-states (EU-15) as well as the new ones (EU-10). A standard Cobb-Douglas production function is employed to estimate lite ICT growth effect in 26 industries, during the 1995-2004 period. The obtained empirical evidence suggests that the overall ICT growth performance was generally insignificant in the EU-15 during 19901995, but improved substantially during 2000-04. Furthermore, returns to ICT were significantly higher in ICT producing industries. On lite other hand, EU-10 industries have benefited from the use of ICT. However, this impact dropped during 2000-2004, while no higher returns seem to exist in ICT producing industries. On the contrary, the ICT growth performance was significantly higher in European service industries that make intensive use of ICT. The results are robust it) possible endogeneity problems.
Keywords: ICT; Panel Data; European Union